SURGICAL TREATMENT OF PATIENTS WITH OSTEOARTHRITIS OF THE KNEE JOINTS - Taras I. Osadchuk; Andrii V. Kalashnikov; Oleg A. Kostohryz; Volodymyr V. Protsenko (Клінічна та профілактична медицина, 2023)
Introduction. Osteoarthritis affects 7 % of the world’s population. The number of affected people worldwide increased by 48 % from 1990 to 2019. At the initial stages of knee osteoarthritis treatment, conservative treatment and corrective osteotomies are used. Corrective osteotomies in the area of the knee joint have shown excellent results for the treatment of limited arthrosis with a predominant lesion of the medial part of the joint in relatively young patients. However, despite the good results reported in the literature, patient satisfaction usually deteriorates over time, and some inevitably require further treatment with total knee arthroplasty in cases of progression of osteoarthritis.